The automated interlingual mapping effect in trainee subtitlers - Deckert, Mikołaj (The Journal of Specialised Translation, 2015)
The paper reports and discusses the findings of an empirical study conducted with trainee subtitlers. As a result of the study, a decision-making pattern has been recognised which is attributed to a cognitive mechanism termed 'automated interlingual mapping' (AIM). The AIM effect is observed in English-to-Polish subtitling data and is postulated to occur when one prototype-based category, and then one verbal node that represents this category, is automatically activated and prioritised as an interlingual match in translation. As the paper seeks to show, the effect is especially salient and intriguing when that prototype/node gets used in the stead of a prototype/node which is more consistent with contextual evidence, and therefore a more optimum target variant.